Homage to Dr. Juan Vigente Ugarte del Pino, outgoing justice and former president of the Supreme Court of Justice, on its ninetieth anniversary - Sánchez-Palacios Paiva, Manuel (2012)
After reviewing some of the work of our honoree, appreciating its magnitude and vastness, those verses by Antonio macHado, popularized by Juan Manuel serrat, came to my memory: "Caminante no hay camino"